Digital Marketing Strategy Review For Business Development - Aprih Santoso; Teti Susilowati; Firman Gazali Djunaidi; Erina Alimin; Sattar Sattar; Siti Intan Nurdiana Wong Abdullah (Lembaga Riset dan Inovasi Al-Matani, 2025)
This study aimed to determine how digital marketing strategies are implemented at XXX Bakery in Semarang City and to identify obstacles, solutions, and existing problems. This study employed a qualitative method with a case study approach, conducted through in-depth interviews, direct observation, and documentation with the XXX Bakery in Semarang City. Data source and data collection were tested for data credibility. Seven participants were used as data sources for the in-depth interviews. The results showed that XXX Bakery in Semarang City implemented its digital marketing strategy through social media platforms like WhatsApp and Instagram, employing the 4P marketing mix: Product, Place, Price, and Promotion. This study identified challenges such as competition and slow order delivery. The solution to these problems was maintaining bread quality and offering attractive promotions. Delays in delivery were addressed by adding dedicated staff and providing time estimates.